Adhesion of bulk-fill resin composites as core and intraradicular post materials only versus the use of glass-fiber posts in different regions of root dentin. Issue 13 (3rd July 2019) - Franz, Martin; Özcan, Mutlu
Abstract: This study assessed adhesion of bulk-fill resin-composites as core and post materials only versus the use of fiber resin composite (FRC) posts. Human teeth ( N  = 84) were cut at the CEJ and endodontically treated and randomly divided into seven groups: TP: Titanium post (Flat Head T); SFRC: S2-glass FRC (Pinpost); EFRC1: E-glass FRC (GC Everstick) directly bonded; GFRC: E-glass FRC (Glassix Nordin); EFRC2: E-glass FRC (Everstick); BF1: Bulk-fill resin (Surefill SDR); BF2: Bulk-fill resin (SonicFill). Groups TP, SFRC, EFRC and GFRC were cemented (Panavia 21), while other groups were bonded directly to the intraradicular dentin. The core parts were constructed using a resin composite (G-aenial) except for Groups BF1 and BF2. The core-cervical dentin interface was loaded under shear forces. Push-out tests were performed in a Universal Testing Machine (1 mm/min). Data (MPa) were analyzed using two-way ANOVA and Tukey`s tests ( α  = 0.05). Not the root level ( p  > 0.05) but the type of core and post material significantly affected shear and push-out bond results ( p  < 0.001). BF1 (9.2 ± 2.1) and BF2 (9.3 ± 3.1) showed significantly lower bond strength to the cervical dentin ( p  < 0.05) compared to other groups (11.6 ± 2.5–19 ± 6.8). FRC post types did not show significant difference being higher than those of TP, BF1 and BF2 (0.57 ± 0.37–2.34 ± 1.98) ( p  > 0.05). Partial cohesive core fracture was more common while BF1 and BF2 showed exclusively adhesive failures. Cohesive failure in the cement was frequent in Group TP (53%) compared to other groups (3–24%). BF1 and BF2 presented exclusively complete adhesive failure of the bulk-fill material.